Pengaruh metode pembelajaran mentorship terhadap keterampilan pemeriksaan Leopold pada mahasiswa DIII kebidanan - Siti Nurbaya; Manapa Esther Sanda; Ahmad Mardiana; Muh.Nasrum Massi; Veni Hadju; Nilawati Andi (Poltekkes Kemenkes Bandung, 2020)
Objective: This study aims to analyze the effect of the mentorship learning method on Leopold's examination skills in midwifery students in Sidenreng Rappang Regency, Madya Pare City, Pinrang Regency, South Sulawesi.Method: This research was conducted in August-September 2019 Sampling was done by purposive sampling technique for Level I students who are active in the Health Sciences High School Study Program D III Midwifery in the Ajateppareng Region from August to September 2019, which were divided into two groups, namely the intervention group of 40 subjects and the control group of 40 subjects, and 80 students were successfully analyzed.Results: The results of the analysis found that the average value of Leopold pre-test skills in the intervention group was 56.32 ± 8.695 and the control group was 50.68 ± 9.683 with a p value = 0.003, while the average value of Leopold skills for post-test female students in the mentorship group was 84.70 ± 4,598 and audiovisual 76,82 ± 6,736 with p = 0,000.Conclusion: There are differences in the mean pretest and posttest scores between the two groups of learning methods, where the method of mentorship learning is generally higher in improving Leopold examination skills in Midwifery DIII students.KEYWORDS: Mentorship; Leopold Examination Skills